Terrestrial Mites of New York (Acarina: Prostigmata), I: Tarsocheylidae, Paratydeidae, and Pseudocheylidae - Delfinado, M. D.; Baker, E. W. (Journal of the New York Entomological Society, 1974)
The mites here described were collected from Long Island, Lake Champlain region, and the Mohawk Valley area, New York, in June-October of 1973. The new species described are: Tarsocheylidae, Hoplocheylus similis, H. americanus; Paratydeidae, Scolotydaeus simplex; Pseudocheylidae, Anoplocheylus transiens. Twenty-six figures are presented. The genus Neotydeus Baker is synonymized with Scolotydaeus Berlese.
Keywords: biology